1998
DOI: 10.1074/jbc.273.44.29015
|View full text |Cite
|
Sign up to set email alerts
|

The Open Reading Frame III Product of Cauliflower Mosaic Virus Forms a Tetramer through a N-terminal Coiled-coil

Abstract: The open reading frame III product of cauliflower mosaic virus is a protein of 15 kDa (p15) that is essential for the virus life cycle. It was shown that the 34 Nterminal amino acids are sufficient to support proteinprotein interaction with the full-length p15 in the yeast two-hybrid system. A corresponding peptide was synthesized and a recombinant p15 was expressed in Escherichia coli and purified. Circular dichroism spectroscopy showed that the peptide and the full-length protein can assume an ␣-helical conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 33 publications
2
45
0
Order By: Relevance
“…Sequence-based secondary-structure predictions indicate that P3 is composed of two amphipathic ␣-helices, with residues 3 to 32 and 38 to 57, respectively, having high and moderate propensities to form coiled-coil structures-a widespread protein-protein interaction and oligomerization motif (1)-thought to be assembled as a parallel tetramer (22,42). The domain organization of the P3 protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sequence-based secondary-structure predictions indicate that P3 is composed of two amphipathic ␣-helices, with residues 3 to 32 and 38 to 57, respectively, having high and moderate propensities to form coiled-coil structures-a widespread protein-protein interaction and oligomerization motif (1)-thought to be assembled as a parallel tetramer (22,42). The domain organization of the P3 protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the two-stranded antiparallel conformation when anchored to virions (37), the N-terminal ␣-helical domain of P3 has been demonstrated to form a distinct coiled-coil structure as a parallel tetramer when free in solution (22). Consistently, a tetrameric form of P3 has been extracted from infected plants (45,46) and also shown to exist in other species of the family Caulimoviridae (42), suggesting a different biological role for this conformation.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, a coiled-coil domain promotes the interaction between the PIII and PII proteins of Cauliflower mosaic virus during transmission by vector aphids (Leclerc et al, 1998 ;Leh et al, 1999). Two mutations of the PEBV TpA56 2b protein are known to severely affect nematode transmission of the virus.…”
Section: Tobraviruses Which Include Pea Early-browning Virus (Pebv)mentioning
confidence: 99%
“…However, studies have suggested that CaMV virions do not appear to directly interact with the MP. Instead, the MP interacts with the CaMV P3 protein (also known as the virion-associated protein [VAP]), which forms a trimeric structure that is anchored into the virions (Leclerc et al, 1998;Leclerc et al, 2001). Electron microscopy studies have indicated that MP and VAP colocalize with virions only at the entrance to or within the plasmodesmata, and it has been suggested that the VAP/virion complex travels to the plasmodesmata independently from the MP (Stavolone et al, 2005).…”
mentioning
confidence: 99%